Propagation Path Effects for Rayleigh and Love Waves (Surface Wave Studies of the Bering Sea and Alaska Area) - Herrin, Eugene; Goforth, Tom; Jin, Doo-Jung (1979)
The area of the Bering Sea and Alaska was studied in terms of shear- velocity, density and compressional-velocity structure by applying a generalized linear inversion method to fundamental-mode Rayleigh-wave group-velocity dispersion relationships in the period range from 10 to 100 sec. Group velocity dispersion relationships in the area were obtained by applying the phase-matched filtering technique to digitally recorded surface-wave data. A new exact analytical method for the computation of Rayleigh-wave phase-velocity partial derivatives with respect to Earth parameters was formulated. With the phase- velocity partial derivatives determined, the group velocity partial derivatives were computed by use of the fast and accurate method of Rodi, and were successfully incorporated into a generalized linear inversion method. In continental Alaska, the crustal thickness is 43 +or- km, and a low velocity zone extendes from a depth of about 113 km to about 213 km. In the Bering Shelf region, the depth to the Mohorovicic discountinuity is 28 +or- 4 km, and a low velocity zone ranges in depth from about 108 km to about 213 km. In the Aleutian Basin, the thickness of the crust is 18 +or- 4 km, and a low velocity zone extends from a depth of about 60 km to about 220 km.